Analisis Literasi Kesehatan Peserta Jaminan Kesehatan Nasional Di Puskesmas Simpang Kawat Kota Jambi - Nina Marinda (Universitas Batanghari Jambi, 2019)
Health literacy determines how well a person's health information to process in achieving desired health outcomes. In the implementation of the National Health Insurance socialization felt still less because there are participants who do not understand about the National Health Insurance. This study aims to determine the participants' health literacy analysis of National Health Insurance. This study uses a Mix Method model of sequential explanatory. Samples were JKN participants in the Puskesmas Simpang Kawat numbering 374 people with Simple random sampling. Where as research informants as many as 11 people were selected by purposive sampling. Quantitative research is known to most of the participants had low health literacy. Bivariate analysis showed a significant correlation between access to health services with literacy health (OR: 4.258, 95% CI 2.756 to 6.579) and there was a significant correlation between access to health information literacy health (OR: 22.864, 95% CI 13.357 to 39.137). In-depth information is obtained that socialization is rarely done and there is no schedule arranged at the center. There is still a lack of understanding of respondents JKN information. Socialization is done by the chief officer of health centers and PIC BPJS. Methods through debriefing and counseling to participants using leaflets media are limited. Puskesmas need to improve understanding JKN information to officers. So that participants can receive access to services at the same access to good information about JKN. This can affect the interaction between the participants in the health service and health centers.